RECENSIONE G. M. D’Allura, R. Faraci, Le imprese familiari. Governance, internazionalizzazione e innovazione, Franco Angeli, Milano, 2018. - Sentuti, Annalisa (Piccola Impresa / Small Business, 2019)
The book reviewed in this issue investigates two important driver of family business development such as internationalization and innovation. The volume is divided into five chapters. The first one focuses on the family business concept. The second concerns the corporate governance of family firms. The third chapter discusses the behaviour of family business in international markets. The fourth chapter regards the family business features concerning innovation. Finally, an empirical chapter based on the case study Cantine Nicosia, provides readers with an in-depth insight into innovation and internationalization strategies of the family firm.